The management of scientific integrity within academic medical centers - Snyder, Peter J., 1964-; Mayes, Linda C.; Smith, William E. (William Edward), 1959- (Amsterdam : Academic Press, an imprint of Elsevier, 2015)
The Management of Scientific Integrity within Academic Medical Centers discusses the impact scientific misconduct has in eight complex case studies. Authors look at multifaceted mixtures of improper behavior, poor communication, cultural issues, adverse medical/health issues, interpersonal problems and misunderstandings to illustrate the challenge of identifying and managing what went wrong and how current policies have led to the establishment of quasi legal processes within academic institutions. The book reviews the current global regulations and concludes with a section authored by a US federal court judge who provides his perspective on the adequacy of current regulations and policies.
Chapter 10 -- Determining the Extent of Data Fabrication Following an Apparent Single Incident.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed Jan. 15, 2015).
Elsevier
Keywords: Academic medical centers -- Corrupt practices; Medicine -- Research -- Moral and ethical aspects; Medicine -- Research -- Corrupt practices; MEDICAL / Research; Electronic books; Electronic books